Chronic Laminitis in a Horse - Treatment with Use of Horseshoe with Horizontal Cross and Epoxy Putty - Strugava, Lucimara; Janiszewski, Jéssica do Rocio; Gomes, Anny Raissa Carolini; Lorga, Andressa Duarte; Wacheski, Fábio; Deconto, Ivan; Moreno, Juan Carlos Duque; Dornbusch, Peterson Triches (Acta Scientiae Veterinariae, 2022)
Background: Laminitis is characterized by an inflammation of the laminar structures of the hoof, which results in lamellar degradation of the suspensory apparatus of the distal phalanx. Despite being a common disease in the equine clinic, it is a medical emergency, which can lead the affected animals not return to sports activities. Due to the severity of laminitis and the poor prognosis, the objective was to report the case of a horse with chronic laminitis with sole perforation in all limbs treated with therapeutic shoeing using a type of horseshoe that has a horizontal crossbar and is filled with mass. Fast-drying epoxy, which has its use little described in the literature Case: A 4-year-old Crioula horse, weighing 325 kg, used in long noose competitions, was referred to the Veterinary Hospital of UFPR with chronic laminitis. The animal had reluctance to move, walk on a trestle position, grade V lameness and phalanx rotation of all limbs. The treatment of laminitis was carried out in the field, for two months, which consisted of trimming and shoeing with a horseshoe in the shape of a heart, and due to the failure of the treatment instituted, the patient presented clinical worsening. The treatment in the HV consisted of cleaning the perforated region of the sole with hydrogen peroxide and 10% iodine and dressing with cotton boots with EVA rubber on the sole to provide comfort. Corrective trimming was performed in order to remove excess forceps, lower the heel, and align the distal phalanx with the hoof wall, using a rasp. Orthopedic shoeing was performed with a normal horseshoe with a horizontal crossbar in the central region. The sole was filled with a quick-drying epoxy putty (Poxilina®), with the aim of preventing sole movement, blocking the rotation of the phalanges and improving the concavity of the hoof. Discussion: In chronic laminitis, the signs observed are claudication and deformation of the hoof, flat sole, enlargement of the white line, uneven growth of the hoof wall, hemorrhage in the abaxial white line, cracks in the hoof wall, which are observed parallel to the coronary band, in addition to phalanx rotation; in this clinical case, all these signs were observed. The trimming of horses with laminitis consists of removing the heels and decreasing the dorsal wall of the hoof, in this case, the trimming performed improved the clinical improvement of the animal five days after the procedure. The horseshoe used in the treatment of this animal has the objective of creating a weight-bearing surface on the middle of the sole, close to the tip of the frog, in this way the weight is not on the supporting edge of the clamp and, in this way, it reduces the pressure. over the most affected area. Despite the scarcity of reports on the use of this type of horseshoe, in this case it played a fundamental role in the treatment of laminitis. In this way, it is an alternative that must be taken into account when choosing the treatment, in view of its effectiveness and lower cost when compared to other methods. This case demonstrates the severity of laminitis in all limbs, especially as it presents a perforation of the sole. It is important to highlight that trimming and shoeing performed at the recommended interval (30-45 days) contributes a lot to the success of the treatment and the return of the animal to sports practice. The horseshoe with a horizontal crossbar was effective in the treatment of chronic laminitis of the forelimbs and pelvic limbs in the reported animal, with progressive improvement of the patient who returned to normal daily activities, without the presence of signs of pain or signs of laminitis after treatment. Keywords: chronic laminitis, horse, sole perforation, recovery. Título: Laminite crônica em equino - tratamento com uso de ferradura com travessa horizontal e massa epóxi. Descritores: laminite crônica, cavalo, perfuração sola, recuperação.